PEMANFAATANTEPUNG TEMPE DENGAN PENAMBAHAN BUBUK KAYU MANISDALAM PEMBUATAN KUKIS DARI SUKUN (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research was conducted to get the best rate and the best quality in the manufacture of a cookie-breadfruit flour, tempe flour and the addition of cinnamon powder. This study was conducted experimentally using a completely randomized design (CRD) with four treatments and four replications thus obtained 16 experimental units. The treatment in this study was TK1 (Tempe flour 23% and Cinnamon powder 2%), TK2 (Tempe flour 20% and Cinnamon powder 5%), TK3 (Tempe flour 17% and Cinnamon powder 8%), TK4 (Tempe flour 14% and Cinnamon powder 11%). Chemical analysis undertaken is the moisture content, ash content, protein content. Data were analyzed statistically to use traditional analysis of variance (ANOVA). If F count is greater than or equal to F table, then do a further test with Duncan's Multiple Range Test (DMRT) at 5% level. Based on the chemical analysis cookie-TK1 best treatment is treatment with water content of 4.91%, levels abu1,67%, 12.11% protein content that has met the cookie-quality standard (SNI 01-2973-1992).   Keywords :Cookies, breadfruit, tempe flour, cinnamon powder